Women Issues and the Problem of Sharia Formalization in Aceh: Disciplining the Female Body and the Contested Public Sphere - Zuly Qodir (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2022)
Abstract: Aceh, with its privileges, has the right to implement Islamic law in the public sphere. Islamic law has become one of the political agendas of local elites and conservative ulama to control women's bodies. This article examines the relationship between women, religion and politics in Aceh and analyzes the relationship between religious-based political interests as a basis for legitimacy for women in the public sphere. The data in this article are based on observations, interviews and documentation as primary data and scientific works as secondary data. Using a political sociology approach and by utilizing the theory of women's body discipline proposed by Michel Faucault, it is concluded that the political interests of conservative groups prevent women from getting their full rights to articulate their political interests in the public sphere. Women occupy a marginal position because of the conservative textual interpretation of religious values. Women are marginalized by prioritizing women's body politics which is considered aurat, so that their involvement in the public sphere is not maximally required. Meanwhile, progressives are trying to fight for women in the public sphere because religion provides opportunities for women's participation. Women do not experience religious discrimination in politics. This is where the contestation takes place between conservatives and progressive groups over the implementation of Islamic law in Aceh.Abstrak: Aceh, with its privileges, has the right to implement Islamic law in the public sphere. Islamic law has become one of the political agendas of local elites and conservative ulama to control women's bodies. This article examines the relationship between women, religion and politics in Aceh and analyzes the relationship between religious-based political interests as a basis for legitimacy for women in the public sphere. The data in this article are based on observations, interviews and documentation as primary data and scientific works as secondary data. Using a political sociology approach and by utilizing the theory of women's body discipline proposed by Michel Faucault, it is concluded that the political interests of conservative groups prevent women from getting their full rights to articulate their political interests in the public sphere. Women occupy a marginal position because of the conservative textual interpretation of religious values. Women are marginalized by prioritizing women's body politics which is considered aurat, so that their involvement in the public sphere is not maximally required. Meanwhile, progressives are trying to fight for women in the public sphere because religion provides opportunities for women's participation. Women do not experience religious discrimination in politics. This is where the contestation takes place between conservatives and progressive groups over the implementation of Islamic law in Aceh.